French image of the inhabitants of the Illyrian Provinces and the emergence of South Slavic nationalisms - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2020)
The Illyrian Provinces, a part of the 1st French Empire which existed in the years 1809-1813, are often portrayed as a political entity which anticipated various projects of the political emancipation of the South Slavs. However, the link between later pan-South-Slavic movements and the Napoleonic political activity is a matter which still remains unclear and deserves some in-depth analysis. Most often the Napoleonic impact on the evolution of the nascent South-Slavic nationalisms is viewed in the perspective of the posterior political attitudes of the Croat, Slovene or Serbian elites towards the French, and their own interpretations of the Napoleonic impact on the pan-South-Slavic movement. The proposed paper will concentrate on the opposite approach and will investigate how French perceived the South Slavs in the perspective of the nascent nationalisms, especially that French propaganda presented Napoleon as the savior of the European nations including the „Illyrian” one. But how French defined this „Illyrian” nation? This question can be answered thanks to the French strive for description of the societies inhabiting Illyrian Provinces.